Economic analysis of the sorghum (Sorghum bicolor L. Moench) value chain in the mid Zambezi Valley of Zimbabwe - Musara, Joseph P. (BUSE, 2020)
Efficient sorghum value chains are integral for sustainability of small scale farmers’subsistence, social and economic livelihoods in semi-arid communities of southern Africa.There is however, a dearth in quantitative evidence on the determinants which are crowding out stakeholders from participating in the sorghum value chain activities. The study added to new knowledge in this realm by analysing the sorghum value chain pillars in the mid-Zambezi Valley of Zimbabwe. Using five Wards from Mbire District, mixed approaches were used to collect cross-sectional survey data from 380 smallholder farmers. Secondary data were collected from Agritex, NGOs, agro-dealers, traders, processors and retailers to triangulate the primary data.Mapping techniques identified relationships, constraints, opportunities and marketing margins accruing to selected sorghum value chain actors. Results from the data show that input supply systems are underdeveloped and production is stalled by the low uptake of improved seed varieties and low fertilizer application. There is limited production, marketing and processing of sorghum due to constrained access to production factors, biased extension services, erratic supply of grain to centralised markets by farmers, limited value addition activities and low producer prices. Determinants of sorghum production and land allocation intensity decisions were examined using double hurdle with probit and censored tobit regression respectively. Frequency of contact with relatives, subsidy access and affiliation toassociations influenced the sorghum production decision. Market access, availability of storage facilities and number of buyers whom the farmer interacts with in the market influenced intensity of land allocation towards sorghum. Factors influencing farmers’ market participation and marketing channel choices were identified using probit and multinomial logit respectively. Three exclusive marketing channels were isolated as local (44.7%), traders (34.2%) and a combination of the two (17.1%). Payment time, number of buyers with whom the farmer relates, age of principal decision maker and distance to market influenced (p<0.05) market participation. Using local market as the referent category, weighted average market price, number of buyers whom the farmer interacts with in the market, distance to the market, dependency ratio and household income are robust determinants of marketing channel selection. Though variables influencing the two decisions are different, showing independence in the decision making processes, information access through interaction with more buyers influenced both decisions. Welfare impacts were then examined using propensity score matching and endogenous switching regression. Household dietary diversity score and household food insecurity access score were adopted as proxies for food security. Sorghum grain physical productivity and net income gains were also used as indicators of household welfare. Counterfactual analysis showed that farmers who allocate more land towards improved sorghum varieties are better off in food diversity, food access, productivity and net returns. Contrary to the hypothesis, the study concludes and adds new knowledge by identifying that, even if stakeholders may have binding backward relationships, they do not necessarily have forward linkages among themselves. The study also concludes that, the various aid dimensions which have not been widely explored, including source, value and the number of beneficiaries are emerging as important factors influencing sorghum production and intensity of production among small scale sorghum farmers. It can be concluded that, household specific, institutional and market factors are important in determining the marketing and marketing channel choices by sorghum farmers in the study area. In line with the hypothesis, there is evidence from the data that, the farmers who adopted and allocated more land towards improved sorghum varieties had higher income, productivity and food security status. It is therefore important to strengthen policies that foster local networks of kinships, cooperative production and marketing and access to aid packages. Investment in appropriate storage facilities in partnership with private players can also reduce post-harvest losses. This allows for sales during market windows of the lean season which usually exhibit higher market prices and help to generate higher returns. Additional research needs to be done with panel data and in other similar semi-arid areas of Zimbabwe over larger spans of time to have a spatial and temporal understanding of the value chain processes.
Keywords: Sorghum value chain; Sorghum production; Sorghum marketing